Dolley Madison papers - Madison, Dolley, 1768-1849.
Correspondence, financial papers, invitations, calling cards, and other papers relating primarily to personal and family matters including settlement of the Dolley Madison, James Madison, and William Madison estates. Includes inventories of household furnishings at Montpelier and Washington, accounts with the grocer, and lists of visitors and visits returned by Dolley Madison. Family correspondents include Anna Payne Causten, R. D. Cutts, John Payne Todd, Rebecca Todd, and Samuel Poultney Todd. Other correspondents include Henry Clay, James Laurie, Elizabeth Collins Lee, John Y. Mason, Henry W. Moncure, Anthony Morris, Phoebe Morris, and Richard Smith.
Microfilm edition available in part
Microfilm produced from originals in the Manuscript Division.
In part, photocopies.
Wife of President James Madison and prominent Washington, D.C., hostess.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Causten, Anna Payne, -- 1819-1852 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Cutts, R. D. -- 1817-1883 -- Correspondence; Laurie, James -- Correspondence; Lee, Elizabeth Collins, -- -1858 -- Correspondence; Madison, Dolley, -- 1768-1849 -- Estate; Madison, James, -- 1751-1836 -- Estate; Madison, William, -- 1762-1843 -- Estate; Mason, John Y. -- 1799-1859 -- Correspondence; Moncure, Henry W. -- 1800-1866 -- Correspondence; Morris, Anthony, -- 1766-1860 -- Correspondence; Morris, Phoebe -- Correspondence; Smith, Richard -- Correspondence; Todd, John Payne, -- 1792-1858 -- Correspondence; Todd, Rebecca -- Correspondence; Todd, Samuel Poultney -- Correspondence; Montpelier (Va. : Estate); Virginia -- Social life and customs; Washington (D.C.) -- Social life and customs; Presidents' spouses -- United States